Corrosion of Conductor Rolls in the Electrogalvanizing Line at Sidercolor - Egli, Walter Alfredo (2012)
After some time in service, conductor rolls in the electrogalvanizing line suffer a surface deterioration that has been attributed to a corrosion-erosion process. This process leads to an increase in roughness and finally produces a pattern on the roll surface that is transferred or copied to the electrogalvanized strip surface originating quality defects that lead to rejections in high quality products. To evaluate the conductor rolls in real working condition, a system to determine conductor roll and steel strip electrochemical potentials was designed. An electrochemical experiment that represents in a better way what happens to the conductor roll surface was developed. Different alloys were submitted to this test and then characterized by Scanning electron microscopy (SEM). It was verified that the intensity and the pattern produced by the electrochemical treatment performed in the laboratory and the superficial attack on the discarded conductor roll were almost the same. This work shows some interesting results that help in the understanding of the nature of this specific corrosion mechanism. A method to evaluate the corrosion resistance of new materials for conductor rolls is also presented. Different alloys were evaluated using this technique.